2023
DOI: 10.3389/fphys.2023.1153900
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single session transcranial direct current stimulation on aerobic performance and one arm pull-down explosive force of professional rock climbers

Abstract: Objective: To explore the effects of single-session transcranial direct current stimulation (tDCS) on aerobic performance and explosive force in the one-arm pull-down of long-term trained rock climbers.Method: Twenty athletes (twelve male and eight female) from the Rock Climbing Team of Hunan province (Hunan, China) were selected for a randomized double-blind crossover study. After baseline tests, All subjects visited laboratories twice to randomly receive either sham or a-tDCS at a current intensity of 2 mA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Grandperrin et al tested participants for vertical jump explosiveness and found that a-tDCS intervention increased the vertical jumping ability of athletes (Grandperrin et al, 2020). Luo et al tested 92 rock climbers with 9 min of incremental aerobic exercise and single-arm pull-down and found that a-tDCS improved the single-arm pull-down explosive power in rock climbers (Luo et al, 2023b Frontiers in Physiology frontiersin.org 20 healthy men to an a-tDCS intervention and measured surface electromyography of the rectus femoris and biceps femoris, which showed that the diameter of the rectus femoris and biceps femoris was significantly higher after real stimulation than after sham stimulation (Lu et al, 2021). Thng et al explored how to improve the level of swimming departure found that swimming departure performance was almost perfectly correlated (r > 0.90) with vertical jump height (Thng et al, 2019); therefore, the present study also included the level of swimming departure in the explosive strength level test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Grandperrin et al tested participants for vertical jump explosiveness and found that a-tDCS intervention increased the vertical jumping ability of athletes (Grandperrin et al, 2020). Luo et al tested 92 rock climbers with 9 min of incremental aerobic exercise and single-arm pull-down and found that a-tDCS improved the single-arm pull-down explosive power in rock climbers (Luo et al, 2023b Frontiers in Physiology frontiersin.org 20 healthy men to an a-tDCS intervention and measured surface electromyography of the rectus femoris and biceps femoris, which showed that the diameter of the rectus femoris and biceps femoris was significantly higher after real stimulation than after sham stimulation (Lu et al, 2021). Thng et al explored how to improve the level of swimming departure found that swimming departure performance was almost perfectly correlated (r > 0.90) with vertical jump height (Thng et al, 2019); therefore, the present study also included the level of swimming departure in the explosive strength level test.…”
Section: Discussionmentioning
confidence: 99%
“…Grandperrin et al tested participants for vertical jump explosiveness and found that a-tDCS intervention increased the vertical jumping ability of athletes ( Grandperrin et al, 2020 ). Luo et al tested 92 rock climbers with 9 min of incremental aerobic exercise and single-arm pull-down and found that a-tDCS improved the single-arm pull-down explosive power in rock climbers ( Luo et al, 2023b ). Lu et al randomly assigned 20 healthy men to an a-tDCS intervention and measured surface electromyography of the rectus femoris and biceps femoris, which showed that the diameter of the rectus femoris and biceps femoris was significantly higher after real stimulation than after sham stimulation ( Lu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation